Development of spatial orientation skills: an fMRI study. - Murias, Kara; Slone, Edward; Tariq, Sana; Iaria, Giuseppe (Brain Imaging & Behavior, 2019)
The ability to orient and navigate in spatial surroundings is a cognitive process that undergoes a prolonged maturation with progression of skills, strategies and proficiency over much of childhood. In the present study, we used functional Magnetic Resonance Imaging (fMRI) to investigate the neurological mechanisms underlying the ability to orient in a virtual interior environment in children aged 10 to 12 years of age, a developmental stage in which children start using effective spatial orientation strategies in large-scale surroundings. We found that, in comparison to young adults, children were not as proficient at the spatial orientation task, and revealed increased neural activity in areas of the brain associated with visuospatial processing and navigation (left cuneus and mid occipital area, left inferior parietal region and precuneus, right inferior parietal cortex, right precentral gyrus, cerebellar vermis and bilateral medial cerebellar lobes). When functional connectivity analyses of resting state fMRI data were performed, using seed areas that were associated with performance, increased connectivity was seen in the adults from the right hippocampal/parahippocampal gyrus to the contralateral caudate, the insular cortex, and the posterior supramarginal gyrus; children had increased connectivity from the right paracentral lobule to the right superior frontal gyrus as compared to adults. These findings support the hypothesis that, as children are maturing in their navigation abilities, they are refining and increasing the proficiency of visuospatial skills with a complimentary increase in connectivity of longer-range distributed networks allowing for flexible use of efficient and effective spatial orientation strategies.